2012
DOI: 10.3390/ijms130810193
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Oxidative Changes in the Kidney of Crucian Carp Induced by Silicon-Based Quantum Dots

Abstract: Silicon-based quantum dots were intraperitoneally injected in Carassius auratus gibelio specimens and, over one week, the effects on renal tissue were investigated by following their distribution and histological effects, as well as antioxidative system modifications. After three and seven days, detached epithelial cells from the basal lamina, dilated tubules and debris in the lumen of tubules were observed. At day 7, nephrogenesis was noticed. The reduced glutathione (GSH) concentration decreased in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…2E). Similar variations were observed previously in fish liver and kidney exposed to other types of xenobiotics (Petrache et al, 2012;Stanca et al, 2013). Recently, it was highlighted that oxidized protein products induced hepatic and renal fibrosis (Li et al, 2014).…”
Section: Oxidative Stress Markerssupporting
confidence: 84%
“…2E). Similar variations were observed previously in fish liver and kidney exposed to other types of xenobiotics (Petrache et al, 2012;Stanca et al, 2013). Recently, it was highlighted that oxidized protein products induced hepatic and renal fibrosis (Li et al, 2014).…”
Section: Oxidative Stress Markerssupporting
confidence: 84%
“…Our current results indicated that protein carbonylation is not a characteristic alteration in silicon-based QD-induced oxidative stress in the liver since protein carbonyls maintained at a basal level (Table 1). Our previous results indicated a decrease in PSH content in the kidney of C. gibelio [70], while in white muscle tissue, this parameter remained unchanged after QDs administration [71]. These differences are probably due to the QDs in vivo distribution, since the liver is a main target…”
Section: Resultsmentioning
confidence: 98%
“…Our previous studies on gibel carp revealed the presence of QDs in the liver [42], kidney [43] and even white muscle tissue [44] as early as 24 h post ip. injection.…”
Section: Discussionmentioning
confidence: 94%